2014
DOI: 10.1371/journal.pone.0089275
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Modal Matching of Audio-Visual German and French Fluent Speech in Infancy

Abstract: The present study examined when and how the ability to cross-modally match audio-visual fluent speech develops in 4.5-, 6- and 12-month-old German-learning infants. In Experiment 1, 4.5- and 6-month-old infants’ audio-visual matching ability of native (German) and non-native (French) fluent speech was assessed by presenting auditory and visual speech information sequentially, that is, in the absence of temporal synchrony cues. The results showed that 4.5-month-old infants were capable of matching native as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
72
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(82 citation statements)
references
References 55 publications
(101 reference statements)
8
72
1
1
Order By: Relevance
“…This evidence indicates that infants’ perception of heard and seen speech is audiovisual from early in life. Moreover, in the first six months of life, infants match audiovisual speech combinations from languages with sounds that are unfamiliar to them (Walton & Bower, 1993; Pons et al, 2009; Kubicek et al, 2014), and even with pairs of non-human animal faces and their vocalizations (Vouloumanos, Druhen, Hauser & Huizink, 2009; Lewkowicz & Ghazanfar, 2006; Lewkowicz, Leo, & Simion, 2010). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This evidence indicates that infants’ perception of heard and seen speech is audiovisual from early in life. Moreover, in the first six months of life, infants match audiovisual speech combinations from languages with sounds that are unfamiliar to them (Walton & Bower, 1993; Pons et al, 2009; Kubicek et al, 2014), and even with pairs of non-human animal faces and their vocalizations (Vouloumanos, Druhen, Hauser & Huizink, 2009; Lewkowicz & Ghazanfar, 2006; Lewkowicz, Leo, & Simion, 2010). …”
Section: Introductionmentioning
confidence: 99%
“…For example, six-month-old Spanish-learning infants look longer at a face articulating/ba/(than a face articulating/va/), when hearing the sound/ba/, and longer at the face articulating/va/when hearing the sound/va/, even though Spanish does not use these two sounds contrastively. However, by 11 months of age, Spanish-learning infants no longer match heard and seen/ba/and/va/, whereas infants learning English—in which the distinction is used contrastively—continue to do so (Pons, et al, 2009; but see Kubicek et al, 2014, for possibly contrasting results with 12-month-olds). While this work could be explained solely on the basis of sensitive periods for the attunement of auditory speech perception, Pons and colleagues (2009) argue that their results may also indicate that perceptual attunement is a “pan-sensory” process.…”
Section: Introductionmentioning
confidence: 99%
“…sequential A and then V displays) up to 11 months of age (e.g., Bristow et al, 2009;Kubicek et al, 2014;MacKain, Studdert-Kennedy, Spieker, & Stern, 1983;Pons, Lewkowicz, Soto-Faraco, & Sebasti an-Gall es, 2009;Walton & Bower, 1993;Yeung & Werker, 2013). sequential A and then V displays) up to 11 months of age (e.g., Bristow et al, 2009;Kubicek et al, 2014;MacKain, Studdert-Kennedy, Spieker, & Stern, 1983;Pons, Lewkowicz, Soto-Faraco, & Sebasti an-Gall es, 2009;Walton & Bower, 1993;Yeung & Werker, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated these questions either by asking whether infants can associate fluent audible and visible speech (Bahrick, Hernandez-Reif, & Flom, 2005; Brookes et al, 2001) or whether they can match one of two faces articulating fluent speech in two different languages with a concurrently presented audible utterance that corresponds to one of the talking faces (Dodd & Burnham, 1988; Kubicek et al, 2014; Lewkowicz & Pons, 2013). These studies have indicated that infants can associate fluent audible and visible speech and that they can match a talking face to a corresponding audible utterance but only when the two are in the infants’ native language.…”
mentioning
confidence: 99%
“…In the three studies in which infants were tested with speech in different languages and which reported that infants can perceive multisensory speech coherence, synchronous auditory and visual information was presented in two of them (Dodd & Burnham, 1988; Kubicek et al, 2014) whereas asynchronous auditory and visual information was presented in the third one (Lewkowicz & Pons, 2013). Moreover, Dodd & Burnham (1988) found that 20-week-old infants can match the faces and voices of their native speech (English) but not non-native speech (Greek) and Kubicek and colleagues (2014) reported that German-learning 12-month-old infants can perceive the identity of their native language as opposed to a non-native language (French). Similarly, Lewkowicz & Pons (2013) found that 10–12 month-old English-learning infants, but not 6–8 month-old infants, can perceive the multisensory identity of a native as opposed to a non-native language (Spanish) when the audible and visible information was not presented concurrently.…”
mentioning
confidence: 99%